2018
DOI: 10.1109/tuffc.2018.2836384
|View full text |Cite
|
Sign up to set email alerts
|

Curvilinear 3-D Imaging Using Row–Column-Addressed 2-D Arrays With a Diverging Lens: Phantom Study

Abstract: A double-curved diverging lens over the flat row-column-addressed (RCA) 2-D array can extend its inherent rectilinear 3-D imaging field of view (FOV) to a curvilinear volume region, which is necessary for applications such as abdominal and cardiac imaging. Two concave lenses with radii of 12.7 and 25.4 mm were manufactured using RTV664 silicone. The diverging properties of the lenses were evaluated based on simulations and measurements on several phantoms. The measured FOV for both lenses in contact with tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…This can be mitigated by employing a lens on the array to both spread out the energy in transmit and make collection of energy outside the rectilinear region possible in receive. Such arrays have been investigated in [43] with lenses in front of the arrays investigated in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…This can be mitigated by employing a lens on the array to both spread out the energy in transmit and make collection of energy outside the rectilinear region possible in receive. Such arrays have been investigated in [43] with lenses in front of the arrays investigated in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum thickness was determined by the arc height between the two lens materials. (5) shows that a large radius, R, was desired as this decreased the arc height, H. For a fixed focal depth, f D , increasing the speed of sound ratio of the outer to the inner lens material, c 2 /c 1 , and of the medium (water/tissue) to the outer lens material c m /c 2 , increases the radius and thereby decreases the arc height.…”
Section: Lens Designmentioning
confidence: 99%
“…For the lens to diverge the beam the speed of sound of material F should be larger than material S. curved diverging lens [4]. In another paper, Bouzari et al presented two concave lenses made from room temperature vulcanizing (RTV) rubber fabricated with two different radii, and it was shown that a FOV up to 44.4 • could be obtained [5]. The downside was that lens shapes were concave, since the RTV rubber had a speed of sound lower than tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The number of elements translates to resolution, contrast, and better signal-to-noise ratio and thus penetration, where a RC array performs better than a matrix array with the same number of elements [3]. Flat RC arrays are limited to a forward-facing field-of-view, which can be remedied by applying a defocusing lens [4], [5]. The imaging performance of RC arrays has been verified by a number of groups [6]- [9], and volumetric 3D vector flow imaging has been demonstrated [10], [11].…”
Section: Introductionmentioning
confidence: 99%